\[\boxed{\text{875\ (875).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = 4x - 7\ \ и\ \ y = - 2x + 11\]
\[4x - 7 = - 2x + 11\]
\[6x = 18\]
\[x = 3\]
\[y = 4 \cdot 3 - 7 = 12 - 7 = 5\]
\[Ответ:(3;5).\]
\[\boxed{\text{875.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[x_{1} - x_{2} = 8;\ \ \ \ \ x_{1}x_{2} = 5\]
\[1)\ x_{1}x_{2}² - x_{1}^{2}x_{2} =\]
\[= x_{1}x_{2}\left( x_{2} - x_{1} \right) =\]
\[= 5 \cdot ( - 8) = - 40\]
\[2)\text{\ x}_{1}² + x_{2}² =\]
\[= x_{1}^{2} + x_{2}^{2} - 2x_{1}x_{2} + 2x_{1}x_{2} =\]
\[= \left( x_{1} - x_{2} \right)^{2} + 2x_{1}x_{2} =\]
\[= 8^{2} + 2 \cdot 5 = 64 + 10 = 74\]
\[3)\ \left( x_{1} + x_{2} \right)² =\]
\[= \left( x_{1} - x_{2} \right)^{2} + 4x_{1}x_{2} =\]
\[= 8^{2} + 4 \cdot 5 = 64 + 20 = 84\]
\[4)\ x_{1}³ - x_{2}^{3} =\]
\[= \left( x_{1} - x_{2} \right)\left( x_{1}^{2} + x_{1}x_{2} + x_{2}^{2} \right) =\]
\[= 8 \cdot \left( \underset{из\ п.2}{\overset{74}{︸}} + 5 \right) =\]
\[= 8 \cdot 79 = 632\]